Developing a Machine Learning-Based Healthcare System to Investigate the Relationship between Depression and Quality of Life (International Journal of Food and Nutritional Sciences, 2022)
Recent technologicaladvancements are reshaping the future of thehealthcare system. Recognizing the factorscontributing to depression is crucial foradvancing research and developing innovativetherapies, given the increasing prevalence ofdepression as a major global public healthconcern